MUHAMMED NURULLAH SEYDA EL-CEZERI’S ATTEMPTS AT THE REVIVAL OF EASTERN MADRASAS AND HIS PAMPHLET NAMELY “USUL AL-TAFSIR” - Mehmet Nurullah AKTAŞ (Fırat University, 2019)
Throughout the history of Islam, there have been penned Usûl al-Tafsir (Methodology of Quranic Interpretation) works, concerning with how to interpret the Quran, the basic resource of Islam. Until recently, although there had been written a considerable number of works on Nahv, Sarf (Arabic Grammar and morphology) and Logic in the eastern madrasas, the publication and taught about Usûl al-Tafsir was strictly limited. This article introduces Muhammed Nurullah Seyda’s biography and scientific personality who lived between 1949 and 1985, and discusses the position of his pamphlet namely “Usûl al-Tafsir” in the revival of eastern and south-eastern madrasas. The pamphlet about “Usûl al-Tafsir”, penned by Muhammed Nurullah Seyda, engaging on knowledge and wisdom has importance in consequence of the fact that it is the first Usûl al-Tafsir work, addressing madrasa students.